Enhancing Spin Coherence in Optically Addressable Molecular Qubits through Host-Matrix Control - S. L. Bayliss; P. Deb; D. W. Laorenza; M. Onizhuk; G. Galli; D. E. Freedman; D. D. Awschalom (Physical Review X, 2022)
Optically addressable spins are a promising platform for quantum information science due to their combination of a long-lived qubit with a spin-optical interface for external qubit control and readout. The ability to chemically synthesize such systems—to generate optically addressable molecular spins—offers a modular qubit architecture which can be transported across different environments and atomistically tailored for targeted applications through bottom-up design and synthesis. Here, we demonstrate how the spin coherence in such optically addressable molecular qubits can be controlled through engineering their host environment. By inserting chromium (IV)-based molecular qubits into a nonisostructural host matrix, we generate noise-insensitive clock transitions, through a transverse zero-field splitting, that are not present when using an isostructural host. This host-matrix engineering leads to spin-coherence times of more than 10  μs for optically addressable molecular spin qubits in a nuclear and electron-spin-rich environment. We model the dependence of spin coherence on transverse zero-field splitting from first principles and experimentally verify the theoretical predictions with four distinct molecular systems. Finally, we explore how to further enhance optical-spin interfaces in molecular qubits by investigating the key parameters of optical linewidth and spin-lattice relaxation time. Our results demonstrate the ability to test qubit structure-function relationships through a tunable molecular platform and highlight opportunities for using molecular qubits for nanoscale quantum sensing in noisy environments.